Effect of taking soduim carbonate dissolved in water at a concentration of lactic acid ratio , in the fifth minute to rest after a maximum effort for the football players in the first division - Aliwi, Ahmed; kadhim, mohammed (Journal of Physical Education, 2014)
Recognize the importance of eating sodium bicarbonate added to the water to increase the physical exertion of the amounts ingested during certain times and certain knowledge of their impact on the pool acid Allaktk. The problem with research in the study of changes in the body by eating sodium bicarbonate added to the water before the performance at the height of the rally lactic acid at rest after the effort. The researcher found that eating bicarbonate reduces the concentration of lactic acid in the blood when measuring the height of lactic gathered at the time of hospitalization. So recommends the use of bicarbonate dissolved in water an hour before the matches in at least reduces fatigue